Spontaneous Object Recognition in the Göttingen Minipig - Anette Moustgaard; Nanna Marie Lind; Ralf Hemmingsen; Axel Kornerup Hansen (Neural Plasticity)
Göttingen minipigs were tested in an object recognition procedure based on spontaneous exploration. Eight pigs were exposed to two similar objects in a sample trial and after a one-hour delay exposed to two objects, one familiar and one novel, in a test trial. The pigs explored the novel object significantly more than the familiar object in the test trial (p<0.05), thereby showing recognition of the familiar object. Furthermore, habituation of exploration of the familiar object between the sample trial and the test trial was found (p<0.05). The procedure can be useful for testing of spontaneous trial-unique memory in pigs.